2010
DOI: 10.1002/chem.200901687
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification and Functionalization of Microporous Hybrid Material for Luminescence Sensing

Abstract: We report here on the preparation of novel luminescent core-shell material by initial coating with polyelectrolytes and subsequent with a silica shell on the lanthanide complexes loaded zeolite L microcrystals. Lanthanide complexes loaded zeolite L was prepared by insertion of 2-thenoyltrifluoroacetone (TTA) into the nanochannels of zeolite crystals by gas diffusion of TTA to Eu(3+) exchanged zeolite L, coating a silica shell on the lanthanide complexes loaded zeolite L resulted to the novel luminescent core-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 181 publications
(296 reference statements)
0
23
0
2
Order By: Relevance
“…[48] Our result is especially surprising and important when confronted with earlier reports regarding Eu 3+ -b-diketonate complexes encapsulated within zeolites. [11,15,17] The mechanism responsible has been elucidated by comparing two different diketonate ligands with different pK a values and two aromatic imines, BPY and PHEN, and by applying stationary and time-resolved spectroscopy. We found that all of the data support the interpretation that the presence of 1 is favorable to the sustainable formation of Eu 3+ -b-diketonate complexes with high coordination numbers by decreasing the proton strength inside of the channels of NZL, the main influence being exerted by the stoppers directly bound to the channel entrance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Our result is especially surprising and important when confronted with earlier reports regarding Eu 3+ -b-diketonate complexes encapsulated within zeolites. [11,15,17] The mechanism responsible has been elucidated by comparing two different diketonate ligands with different pK a values and two aromatic imines, BPY and PHEN, and by applying stationary and time-resolved spectroscopy. We found that all of the data support the interpretation that the presence of 1 is favorable to the sustainable formation of Eu 3+ -b-diketonate complexes with high coordination numbers by decreasing the proton strength inside of the channels of NZL, the main influence being exerted by the stoppers directly bound to the channel entrance.…”
Section: Methodsmentioning
confidence: 99%
“…[14] We and others observed considerable improvement of thermal-and photostability of lanthanide complexes when embedding them in the channels of zeolite L (ZL). [15][16][17][18][19][20][21] Oriented Ln 3+ doped ZL films with tunable emission colors have been synthesized by using functional linkers that can coordinate and sensitize Ln 3+ . [22,23] Increasing effort has been focused on nanosized zeolite for a variety of reasons.…”
mentioning
confidence: 99%
“…5À8 Indeed, conventional synthesis usually yields bis-(hydrated) tris(β-diketonates), but the two solvent molecules can be effortlessly substituted by either a fourth diketonate anion or a bidentate donor ligand which may be functionalized so as to provide convenient light-harvesting and subsequent energy transfer onto the metal ion. Lanthanide β-diketonates and their derivatives are amenable to incorporation into all kind of materials, from thin films, 9 to ionic liquids, 10 mesoporous 11 or microporous 12 hybrids, and nanoparticles. 13 The unmatched luminescent properties of β-diketonate compounds and materials are at the heart of a number of applications, ranging from analytical sensors, 14À16 emissive layers for organic light-emitting diodes (OLEDs), 17À19 including white-light production, 20,21 nonlinear optics, 22 as well as time-resolved bioanalyses 23 and bioimaging.…”
mentioning
confidence: 99%
“…Зокрема, під час концентрування Gd(III) допустимий кратний вміст (С іон /С Gd(III) ) SO 4 2-, NO 3 -, Cl -, K + , Na + перебуває в межах 1 000-2 500. Такі високі вмісти цих іонів не впливають на значення максимальної сорбційної ємності клиноптилоліту стосовно Gd(III).…”
Section: таблиця 2 ефективність десорбції Gd(iii) з клиноптилолітуunclassified